Developmental trajectories of adolescent risky drinking: predictors from the Drug Education in Victoria Schools (DEVS) study. Issue 4 (3rd September 2018) - Lester, Leanne; Midford, Richard; Foxcroft, David; Cahill, Helen
ABSTRACT: With alcohol misuse one of the leading causes of disability among young Australians, determination of potential predictors of risky drinking trajectories of young people is crucial. This study aimed to identify risky drinking trajectories from early to mid-adolescence and to determine if membership of a harm minimization intervention, alcohol knowledge, attitudes towards alcohol and prevalence of alcohol harms would predict trajectory group membership. Longitudinal data from 1746 students were used to identify alcohol consumption trajectory groups for both intervention and control students. Higher baseline knowledge predicted a higher, increasing, consumption trajectory for controls, whereas, safer attitudes at baseline were not associated with a higher, increasing trajectory. All other alcohol harms at baseline were strongly associated with higher consumption trajectories. The intervention group had fewer increasing trajectories and a lower level of consumption at the end of the programme, suggesting the drug education programme reduced the number of students who substantially increased their consumption over time, while at the same time reducing their level of consumption in relative terms. The consistency of better intervention student outcomes across all trajectories provides evidence that the drug education programme was influential with all types of student drinkers and is suitable for universal delivery.